Metric regularity of the sum of multifunctions and applications - Huynh Van Ngai; Huu Tron Nguyen; Michel Théra (My University, 2014)
Metric regularity of the sum of multifunctions and applications
Keywords: Sum of multifunctions; Metric regularity; Applications